Adapting a Remote SDR Lab to Analyze Digital Inequalities in Wireless Communications Education in Latin America (Innovaciones Educativas, 2023)
The introduction of technological tools in education has generated environments that simplify the transmission of knowledge to students. However, not everyone has equal access to these tools and several studies have investigated the factors of this digital divide. Specifically, in engineering education, remote laboratories are gaining ground by offering the opportunity to experiment with specialized equipment remotely from anywhere via the Internet. As these labs become increasingly integrated into university curricula, they can also generate digital inequalities among the student body, due to their advanced hardware and software knowledge requirements. The main purpose of this paper is to adapt the Remote Engineering Laboratory for Inclusive Access (RELIA), which operates Software Defined Radio (SDR) technology devices, to the Latin American context, to address and study in the future the digital inequalities that remote laboratories generate in radio frequency education in Latin America. To achieve this, a methodology has been employed that identifies the needs of the Latin American audience through a literature review that explores the existing literature on digital inequalities in the United States and Latin America. In addition, as a future objective, it is planned to compare these findings with similar research and surveys conducted in the United States.
Keywords: Digital inequality; Equal access; Remote laboratories; Software Defined Radio (SDR); Wireless communications; RHL-RELIA